Aerospace Instrumentation and Control Systems: Challenges, Innovations, and Future Prospects - Kapoor, Megha (Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
Aerospace systems rely heavily on sophisticated instrumentation and advanced control mechanisms to ensure precision, safety, and efficiency in extreme environments characterized by high altitudes, intense radiation, vast temperature variations, and unpredictable dynamics. As aerospace missions become increasingly complex—ranging from commercial aviation to interplanetary exploration—the demands on instrumentation accuracy, system autonomy, data management, and fault tolerance have intensified. This review discusses the current challenges faced in aerospace instrumentation and control, including environmental resilience, precision under dynamic conditions, secure communication, and real-time decision-making. It highlights recent innovations such as smart miniaturized sensors, AI-driven adaptive control systems, fiber optic sensor networks, and fault-tolerant architectures that are transforming the aerospace sector. Emerging trends like quantum sensing, autonomous spacecraft navigation, integrated structural health monitoring, and cybersecurity advancements are also explored. By synthesizing developments across sensor technologies, autonomous control, artificial intelligence (AI) integration, and cybersecurity, this article provides a comprehensive overview of the field. The review concludes by identifying critical opportunities for research and development that could shape the next generation of aerospace systems, emphasizing the importance of interdisciplinary collaboration to overcome existing barriers and propel aerospace engineering into a new era of innovation.